2013
DOI: 10.1152/ajpregu.00221.2012
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of dystrophic skeletal muscle by PGC-1α involves restored expression of dystrophin-associated protein complex components and satellite cell signaling

Abstract: Duchenne muscular dystrophy is typically diagnosed in the preschool years because of locomotor defects, indicative of muscle damage. Thus, effective therapies must be able to rescue muscle from further decline. We have established that peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Pgc-1α) gene transfer will prevent many aspects of dystrophic pathology, likely through upregulation of utrophin and increased oxidative capacity; however, the extent to which it will rescue muscle with diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 66 publications
(99 reference statements)
6
73
0
Order By: Relevance
“…One approach to this target is gene therapy. Recent reports have suggested that viral or plasmid delivery of PGC-1α post-natally can improve muscle function in mdx mice [32,63]. Our data support this conclusion, and show that PGC-1α expression specifically in myotubes likely mediates this protection.…”
Section: Discussionsupporting
confidence: 89%
“…One approach to this target is gene therapy. Recent reports have suggested that viral or plasmid delivery of PGC-1α post-natally can improve muscle function in mdx mice [32,63]. Our data support this conclusion, and show that PGC-1α expression specifically in myotubes likely mediates this protection.…”
Section: Discussionsupporting
confidence: 89%
“…Autophagy emerges then as an essential process for the clearance of defunct cellular organelles and a continued inhibition of autophagy exaggerates dystrophic phenotype (Hindi et al, 2014). The beneficial effects of activating autophagy in mdx mice have been also confirmed by overexpressing peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1a), a transcriptional coactivator, which is a powerful mediator of muscle plasticity (Hollinger et al, 2013) and by pharmacological treatment with an agonist drug against the energy sensor AMPK, i.e., 5-aminoimidazole-4-carboxamide-1-β- d -ribofuranoside (AICAR) (Pauly et al, 2012). In particular, AICAR treatment led to a significant activation of the autophagy, as indicated by the characteristic biochemical changes of increased lipidated LC3 content, an upregulation of other prototypical autophagy-associated proteins, and to significant improvements in both muscle structure and maximum force-generating capacity (Pauly et al, 2012).…”
Section: Deregulation Of Autophagy In Duchenne Muscular Dystrophymentioning
confidence: 99%
“…; Hollinger et al . ; Hollinger & Selsby, ). In many regards this approach mimics the effects of endurance exercise, which is controversial in DMD patients due to the potential for increased injury (Carter et al .…”
Section: Introductionmentioning
confidence: 99%